Penerapan nilai karakter tanggungjawab siswa Sekolah Dasar di lingkungan keluarga - Nugroho, Irfan Adi; Nartani, C. Indah; Nofrida, Eka Ridha; Amalia, Sholihati (Journal of Contemporary Issues in Primary Education, 2023)
This study aims to: 1) describe the character value of responsibility in the family environment; 2) describe the strategy of presenting the character value of responsibility in the family environment. The expected output of this study is a research report related to character values in thematic learning in low-grade elementary schools and publications in scientific journals. The research method used is a qualitative descriptive method with the researcher as the key instrument. Data collection is carried out by the note-taking method. Data analysis is qualitative descriptive. The object of research is students and parents at the elementary school level in the city of Yogyakarta. Data analysis includes data reduction, data presentation, data verification, and triangulation. The results of this study show that character education, especially character responsibility has been implemented in the family. What is done is more directing than commanding and even scolding.